(untitled) (Raparin Journal of Humanities (RJH), 2024)
The aim of this study is to determine the relationship between the level of teaching performance and teaching profession among teachers of Koya University. (90) teachers participated randomly from different departments of the faculty of Education. Two data collection tools were used, the first measuring the level of teaching performance, and the second to measure the teachers’ attitudes toward teaching profession The reliability of the first instrument was (0.75), and for the second was (0.74). The research used statistical software (SPSS) to analyze the data. The result showed a statistically significant positive relationship between the level of teaching performance and teachers’ attitudes toward teaching profession. finally, several recommendations and suggestions were presented.